Financial Literacy in the Millenial Workforce Padang - Putri, Annisa Nabila; Friyatmi, Friyatmi (Lembaga Yasin AlSys, 2023)
Financial management behavior millenial workforce Kota Padang is still relatively low. The lack of ability to set aside some of his income for savings and also the low ability to make budgets and expenditures are the causes. The purpose of the study was to analyze the effect of Financial Literacy on the Financial Management Behavior of millennial workforce Padang. Type of quantitative research with causative research design. Primary data was obtained through the distribution of online questionnaires using google form to research samples. The sampling technique uses purposive sampling techniques and with the slovin formula gets a sample of 100 respondents. The data were analyzed using multiple linear regression analysis with the help of the SPSS 26 program. The results revealed that Financial Literacy has a positive and significant effect on the Financial Management Behavior of millennial workforce Padang. If someone has a high level of financial literacy, Financial Management Behavior will also be high.